Book Review: Canadian Curriculum Studies: A Métissage of Inspiration/Imagination/Interconnection - Downey, Adrian (Journal of the Canadian Association for Curriculum Studies, 2020)
This text comprises a book review of Canadian Curriculum Studies: A Métissage of Inspiration/Imagination/Interconnection, edited by Erika Hasebe-Ludt and Carl Leggo (2018) and published by Canadian Scholars’ Press. In this text, I first summarize the main themes and trends of the volume through reference to specific, illustrative contributions. I also highlight the rather distinct structure of the volume. In my discussion of the volume, I articulate its usefulness to emerging curriculum scholars as well as those teaching graduate courses in curriculum studies. I also make reference to several questions I have after reading the book as a whole. Finally, I end this essay by pointing to the intimate and welcoming atmosphere of the volume and of Canadian curriculum studies more generally.